Arachidonic acid and calcium metabolism in rnelittin stimulated neutrophils - Ole H. Nielsen; Pierre N. Bouchelouche; Dag Berild (Hindawi Limited, 1992)
Melittin, the predominant fraction of bee venom proteins, was studied in an experimental model of human neutrophil granulocytes to reveal its influence on eicosanoid release, metabolism and receptor function in relation to intracellular calcium metabolism. Melittin (2 μmol/l) was as potent as the calcium ionophore A23187 (10 μmol/l) for activation of 5-lipoxygenase, releasing arachidonate only from phosphatidyl-choline and phosphatidyl-ethanolamine of cellular membranes, as judged from the decreases in radioactivity by 15.4% and 30.5%, respectively. The mechanism responsible for the release of arachidonate from cellular membranes is closely coupled to cellular calcium metabolism, and melittin was found to promote calcium entry through receptor gated calcium channels, probably due to an activation of phospholipase A2. Furthermore, a down-regulation of leukotriene B4 receptors was seen. The maximal number of binding sites per cell was reduced from a median of 1520 to 950 with melittin (1 μmol/l). The study has revealed some factors important for the inflammatory mechanisms mediated by melittin.